The Alcatraz escape - Bertman, Jennifer Chambliss (Bertman, Jennifer Chambliss. Book Scavenger., 2019)
Emily and James compete in an epic escape-room challenge on Alcatraz Island, designed by game-maker Garrison Griswold and mystery writer Errol Ray. Soon, James and Emily discover that they are being targeted, and uncover a dangerous plot involving Emily's brother, Matthew. They must then solve the mystery that will lead them to the saboteur while also trying to escape the harrowing Alcatraz underground.